2017
DOI: 10.1063/1.4974200
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric properties of orthorhombic group IV–VI monolayers from the first-principles calculations

Abstract: Two-dimensional (2D) materials may have potential applications in thermoelectric devices. In this work, we systematically investigate the thermoelectric properties of orthorhombic group IV-VI monolayers AB (A=Ge and Sn; B=S and Se) by the first-principles calculations and semiclassical Boltzmann transport theory. The spin-orbit coupling (SOC) is included to investigate their electronic transport, which produces observable effects on power factor, especially for n-type doping. According to calculated ZT , the f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(58 citation statements)
references
References 47 publications
(63 reference statements)
3
54
0
1
Order By: Relevance
“…From theoretical reports, the number of studies has been consistently increasing in the last decade, and several studies of 2D materials related to this field and presented in this work have been recently reported. For both experimental and theoretical studies, we found a fairly reasonable agreement of electrical properties with our reported values (Kumar and Schwingenschlögl, 2015;Sun et al, 2015;Morales Ferreiro et al, 2016;Tyagi et al, 2016;Ding et al, 2017;Guo and Wang, 2017;Li et al, 2017;Shafique and Shin, 2017).…”
Section: Te Propertiessupporting
confidence: 87%
See 3 more Smart Citations
“…From theoretical reports, the number of studies has been consistently increasing in the last decade, and several studies of 2D materials related to this field and presented in this work have been recently reported. For both experimental and theoretical studies, we found a fairly reasonable agreement of electrical properties with our reported values (Kumar and Schwingenschlögl, 2015;Sun et al, 2015;Morales Ferreiro et al, 2016;Tyagi et al, 2016;Ding et al, 2017;Guo and Wang, 2017;Li et al, 2017;Shafique and Shin, 2017).…”
Section: Te Propertiessupporting
confidence: 87%
“…Since SOC has been reported to have the possibility of influencing the electronic transport in TEs (Guan et al, 2015;Guo and Wang, 2017), we computed the electronic structures for GeS, GeSe, SnS, SnSe, SnS2, and SnSe2 without and with SOC. The band structures are shown in Figure 3.…”
Section: Results and Discussion Band Structuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Tin sulfide SnS, which in the bulk form is a semiconductor with a layered structure, can be split into monolayers and nanoplatelets by chemical methods. [5][6][7] The interest to SnS quasi-2D structures is stimulated by their thermoelectric, electric, and optical properties [8][9][10][11][12][13][14][15][16][17] and the predicted ferroelectricity in SnS monolayers. 18,19 The latter suggests a possible application of piezoelectric properties of these structures.…”
Section: Introductionmentioning
confidence: 99%